WAVE TESTS AND NONLINEAR REGRESSION ANALYSIS FOR ESTIMATION OF HYDRODYNAMIC COEFFICIENTS FOR OFFSHORE JACKET PLATFORMS - AMAL, SEBASTIAN ALEX (2014)
Adaptations in the design and reliability analysis of jacket platforms are gaining importance in the economical perspective, due to the discovery ofnew shallow water oil fields and aging of existing oil and gas assets. This research is focused on improving the design of offshore jacket platforms by the conclusions and recommendations made from an experimental study on the hydrodynamic force coefficients. Majority ofthe members on ajacket platform are slender cylinders with circular cross-section. Critical part in the estimation ofwave forces on small diameter cylindrical structures employing Morison equation, is the determination of precise hydrodynamic force coefficients. Wave tank tests were conducted in the offshore laboratory facility of Universiti Teknologi PETRONAS. Model cylinders were tested in both regular and random, unidirectional waves. Total wave forces acting on the model cylinders were measured by a wave force sensor named Wave Force Totaller, which was developed exclusively for use in the experimental works reported.